2006
DOI: 10.1073/pnas.0507924103
|View full text |Cite
|
Sign up to set email alerts
|

A genetic locus required for iron acquisition in Mycobacterium tuberculosis

Abstract: Mycobactins are a family of membrane-associated siderophores required for Mycobacterium tuberculosis to adapt to its intracellular habitat. These lipophilic siderophores have been recently shown to directly acquire intracellular iron through lipid trafficking. Despite tremendous progress in understanding the assemblyline enzymology of the siderophore biosynthesis, the genes as well as the mechanistic and biochemical principles involved in producing membrane-associated siderophores have not been investigated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
130
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 39 publications
3
130
0
Order By: Relevance
“…Seminal work showed that mycobactin synthases, named MbtA-N, are encoded at two loci (6,9,10). IdeR controls siderophore biosynthesis by repressing transcription of mbtA-N in iron-replete conditions (9)(10)(11). The predicted functions of MbtA-N fit well into widely accepted theoretical models for the production of mycobactin, but the functions of most genes and intermediates in mycobactin biosynthesis have not been directly established (5,6,9,10).…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Seminal work showed that mycobactin synthases, named MbtA-N, are encoded at two loci (6,9,10). IdeR controls siderophore biosynthesis by repressing transcription of mbtA-N in iron-replete conditions (9)(10)(11). The predicted functions of MbtA-N fit well into widely accepted theoretical models for the production of mycobactin, but the functions of most genes and intermediates in mycobactin biosynthesis have not been directly established (5,6,9,10).…”
mentioning
confidence: 76%
“…First, they are high-affinity, hexadentate iron ligands. Second, they neutralize the Fe 3+ cation and tether it to a lipid tail, promoting iron transport across the hydrophobic membranes (8)(9)(10). Both lipids contain the same peptide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Iron is a cofactor for numerous heme and non-heme proteins that are involved in critical metabolic functions that are common to all living organisms (21,22). M. tuberculosis like other pathogenic bacteria has evolved complex mechanisms to acquire host iron which is limited in vivo even under normal physiologic conditions (30,31,45,46). It was the observations from in vitro studies, that M. tuberculosis can scavenge host iron that led us to hypothesize that iron accumulated in the primary lung lesions in the guinea pig model of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%